2010
DOI: 10.1128/jvi.01894-09
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Dose Influenza A (H5N1) Vaccine Safe and Immunogenic in Adult and Elderly Patients: an Approach to Pandemic Vaccine Development

Abstract: With the ongoing pandemic of influenza A (H1N1) virus infection and the threat of high fatality rates for recent human cases of infection with highly pathogenic H5N1 strains, there has been considerable interest in developing pandemic vaccines. Here we report a randomized multicenter dose-finding clinical trial of a whole-virion, inactivated, adjuvanted H5N1 vaccine in adult and elderly volunteers. Four hundred eighty patients were randomly assigned to receive one or two doses of 3.5 g of the vaccine or one do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 22 publications
(36 reference statements)
1
31
0
1
Order By: Relevance
“…The use of safe and effective adjuvants in pandemic influenza virus vaccines is considered a dose-sparing strategy. Clinical trials evaluating candidate inactivated influenza A/H5N1 virus vaccines showed that the use of adjuvants can increase their immunogenicity and broaden the specificity of the induced antibody responses (2,7,19,23,27,36,41). These research efforts have resulted in the licensing of adjuvanted vaccines against seasonal and pandemic influenza viruses (17).…”
mentioning
confidence: 99%
“…The use of safe and effective adjuvants in pandemic influenza virus vaccines is considered a dose-sparing strategy. Clinical trials evaluating candidate inactivated influenza A/H5N1 virus vaccines showed that the use of adjuvants can increase their immunogenicity and broaden the specificity of the induced antibody responses (2,7,19,23,27,36,41). These research efforts have resulted in the licensing of adjuvanted vaccines against seasonal and pandemic influenza viruses (17).…”
mentioning
confidence: 99%
“…The reduced-dose vaccine (Fluval K, an inactivated, wholevirion, trivalent vaccine with 6 g of HA/strain/0.5 ml content and aluminum phosphate gel adjuvant; lot no. FL-K-004) was produced by Omninvest Ltd. (Budapest, Hungary) as described previously (8,(14)(15)(16)(17)(18)(19). With the exception of the antigen amount, the vaccine was prepared by the same method as for the licensed seasonal influenza vaccine Fluval AB (19) and the licensed prepandemic vaccine Fluval H5N1 and the licensed pandemic H1N1 vaccine Fluval P (8,(14)(15)(16)(17)(18).…”
Section: Methodsmentioning
confidence: 99%
“…We recently tested aluminum phosphate-adjuvanted whole-virion, monovalent prepandemic H5N1 and pandemic H1N1 influenza vaccines with only 6 g of HA and found them to be safe and immunogenic in pediatric, adult, and elderly subjects (8,(14)(15)(16)(17)(18). We also found that doses of 3.5 g did not trigger sufficient immune responses, while doses of 12 g were not substantially more immunogenic than 6-g doses when using monovalent vaccines (15). Thus, based on our experience with monovalent vaccines, the objective of this study was to evaluate the safety and immunogenicity of a trivalent seasonal influenza vaccine with 6 g HA/ strain in adult and elderly subjects.…”
mentioning
confidence: 99%
“…A használt technológia mellett a hatóanyag-tartalom növelése az immunválaszban további növekedést nem okozott [7]. A fejlesztést alátámasztotta az általunk korábban, szintén 6 µg hatóanyag-tartalmú pandémiás (H1N1) influenzavakcinákkal folytatott klinikai vizsgálatok eredménye, valamint a 2009. évi pandémia idején alkalmazott oltó-anyag vírusfertőzéssel szembeni hatékonysága [5][6][7][12][13][14][15]. A klinikai vizsgálati készítmények eredményei alapján az új, 6 µg hatóanyag-tartalmú készítmény forgalomba hozatali engedély megszerzését követően (OGYI-T-8998/03) a 2015/2016-os szezonban került először a piacra, 3FluArt néven.…”
unclassified